Porosity Evolution In Lacustrine Organic-Matter-Rich Shales With High Claly Minerals Content - Jiang, Xiaohua; Wu, Songtao; Hou, Lianhua; Zhang, Jinyou; Guan, Modi; Zhai, Fulin; Guo, Jinhao; Su, Ling; Liao, Fengrong; Ding, Lihua (Frontiers in Earth Science, 2021)
Pore structure is a major factor affecting the storage space and oil-bearing properties of shales. Mineralogy, organic matter content, and thermal evolution complicate the pore structures of lacustrine shales. In this study, the porosity evolution of organic-matter-rich shales from the Cretaceous Nenjiang Formation in the Songliao Basin, Northeast China, are investigated using thermal simulation experiments and in-situ scanning electron microscope analysis. Three findings were obtained as follows: 1) The pore system of shales from the Nenjiang Formation is dominated by inter-granular dissolution pores of plagioclase and intra-granular pores of illite-smectite mixed layers. Few organic-matter pores are observed. 2) New pores developing during thermal evolution are primarily organic matter pores and clay mineral pores, with diameters greater than 18 nm. Clay mineral pores with diameters of 18–50 nm are the principal contributors to porosity at temperatures between the low maturity stage and the oil-generation window, and organic matter pores with diameters of greater than 50 nm comprise the majority of pores generated between the gas-generation window and the high-/over-mature stages. 3) Porosity increases continuously with maturity, and the pore system varies at different maturity stages. Porosity evolution is controlled by illite content and organic matter abundance. Total pore volume correlates positively with illite content but negatively with organic matter abundance. These findings could provide guidance on shale oil evaluation in the Songliao Basin and assist in the ‘sweet-spotting’ of lacustrine shale systems across China.